1991
DOI: 10.1007/bf03350283
|View full text |Cite
|
Sign up to set email alerts
|

Anti-bovine thyrotropin autoantibodies in patients with Hashimoto’s thyroiditis, subacute thyroiditis, and systemic lupus erythematosus

Abstract: We report four cases found to have anti-bovine thyrotropin (bTSH) antibodies, two with Hashimoto's thyroiditis and the other two, each with subacute thyroiditis and systemic lupus erythematosus (SLE). The unusually high negative titers of anti-TSH receptor antibodies (Case no. 1, -43.1%; Case no. 2, -34.9%; Case no. 3, -55.2%; Case no. 4, -59.9%) led to the incidental finding of the presence of anti-bovine (bTSH) antibodies in each patient. Case no. 1 was diagnosed to have Hashimoto's thyroiditis and was treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Although the significance of the presence of and-bTSH antibodies in our patient still remains to be elucidated, the fact that such antibodies were found in the sera from thyroidal disorders other than Graves' disease and in a non-thyroidal illness (PSS) supports the view that the bTSH antibodies recognized with the TRAb kit are not specific for Graves' disease alone [16]. Although none of the authors has hitherto reported a similar case, it is interesting that the recovery from silent thyroiditis in this patient was associated with the concomitant disappearance of anti-bTSH antibodies.…”
Section: Discussionsupporting
confidence: 60%
“…Although the significance of the presence of and-bTSH antibodies in our patient still remains to be elucidated, the fact that such antibodies were found in the sera from thyroidal disorders other than Graves' disease and in a non-thyroidal illness (PSS) supports the view that the bTSH antibodies recognized with the TRAb kit are not specific for Graves' disease alone [16]. Although none of the authors has hitherto reported a similar case, it is interesting that the recovery from silent thyroiditis in this patient was associated with the concomitant disappearance of anti-bTSH antibodies.…”
Section: Discussionsupporting
confidence: 60%
“…The existence of bTSH binding antibodies has been reported in Graves' disease and other thyroid disease (Hashimoto's thyroiditis, silent thyroiditis, and subacute thyroiditis) by the unusual negative values in the assay of TRAb (1)(2)(3)(4)(5)(6)(7)(8)(9). With regard to the incidence in Graves' disease 2% (2 of 102) (1), 1.3% (2 of 154) (2), 0.4% (21 of 4285) (7), and 0.32% (8 of 2500) (8) have been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Although the improvement of the sensitivity of TRAb determination by the calculation using the determined NSB(T) of each test There are many reports of abnormally negative TSH serum has been reported, the determination of precise receptor antibody (TRAb) activity in the TSH recep-TRAb activity was difficult in cases with abnormally negtor assay caused by antibodies to bovine TSH (bTSH) ative TRAb values without absorption of the bTSH bind- (1)(2)(3)(4)(5)(6)(7)(8)(9). Thus, the precise evaluation of TRAb activity in ing antibody (10).…”
mentioning
confidence: 99%
“…Evidence has accumulated [2, 3, 4, 5, 6, 7, 8]that anti-TSH antibodies in Graves’ patients (had never received exogenous TSH) have higher binding to animal TSH such as bTSH or pTSH than hTSH. Previously, we demonstrated that anti-TSH antibody bound specifically with the α-subunit of pituitary glycoprotein hormone (TSH, LH, FSH) in spite of no binding of TSH(β) [9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of anti-thyroid-stimulating hormone (TSH) antibodies in Graves’ disease and other thyroidal diseases (Hashimoto’s thyroiditis, silent thyroiditis, subacute thyroiditis) has been reported [1, 2, 3, 4, 5, 6, 7, 8]. We have previously described the characteristics of anti-TSH antibodies in the serum of 2 patients with Graves’ disease [2].…”
Section: Introductionmentioning
confidence: 99%